Species Diversity and Population Structure of Fishes in the Phrom River, Chaiyaphum Province, the Northeastern Region of Thailand - Petsut, Nidsaraporn; Kulabtong , Sitthi; Petsut , Jirawaeth (Burapha Science Journal, 2026)
Species diversity and population structure of fishes in the Phrom River, Chaiyaphum Province, the northeastern region of Thailand, this study provides an essential basis for the biodiversity and ecology of fish species in the Phrom River area. The study will lead to effective and sustainable management of fisheries resources, application, and conservation of aquatic animal resources in the area. The study carried out in the period dry seasons (March) and rainy seasons (June) 2014. From the results of the study, it was found 265 collected specimmens. In this survey, fish specimens were collected by beach seine and dip-net. A total of 28 species from 15 families of fish resources were found. Cyprinidae is a dominant family in species number and inferior to Osphronemidae. In the part of population structure, in March 2014, the average abundance of fish population found that between 0.05–0.57 individuals/m.2 and in June 2014, the average abundance of fish population found that between 0.22–1.20 individuals/m.2. The highest average fish product is about 30.10 and 33.29 Kilograms/Rai. (dry seasons and rainy seasons) Siamese glassfish (Parambassis siamensis) and Nile Tilapia (Oreochromis niloticus) are dominant species in this area. The data of diversity index, evenness index and dominance index of fish specimens showed that, the fish specimens in collecting site were moderate diversity (Hʹ; 0.90–2.09). The distribution of fish specimens in upper basin were not evenness and some fish specimens are dominance more than other specimens in each collecting sites, but the distribution of fish specimens in lower basin were evenness.